The Evolution and Fossil Record of Parasitism: Coevolution and Paleoparasitological Techniques - de Baets, Kenneth; Huntley, John Warren (Springer, 2021)
This two-volume edited book highlights and reviews the potential of the fossil record to calibrate the origin and evolution of parasitism, and the techniques to understand the development of parasite-host associations and their relationships with environmental and ecological changes. The book deploys a broad and comprehensive approach, aimed at understanding the origins and developments of various parasite groups, in order to provide a wider evolutionary picture of parasitism as part of biodiversity. This is in contrast to most contributions by parasitologists in the literature that focus on circular lines of evidence, such as extrapolating from current host associations or distributions, to estimate constraints on the timing of the origin and evolution of various parasite groups. This approach is narrow and fails to provide the wider evolutionary picture of parasitism on, and as part of, biodiversity. Volume two focuses on the importance of direct host associations and host responses such as pathologies in the geological record to constrain the role of antagonistic interactions in driving the diversification and extinction of parasite-host relationships and disease. To better understand the impact on host populations, emphasis is given to arthropods, colonial metazoans, echinoderms, mollusks and vertebrates as hosts. In addition, novel techniques used to constrain interactions in deep time are discussed ranging from chemical and microscopic investigations of host remains, such as blood and coprolites, to the statistical inference of lateral transfer of transposons and host-parasite coevolutionary dynamics using molecular divergence time estimation.
Keywords: Identifying parasitism in the fossil record; viral fossils; Protistan parasites; Insects as parasitoids and parasites; extinct lineages of parasites; Evolutionary history; Co-divergence; host response; Paleoparasitology techniques; Parasite-induced traces; Molecular perspectives